MEKANISME GOOD CORPORATE GOVERNANCE TERHADAP NILAI PERUSAHAAN PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA - gina septiana; Aminar Sutra Dewi (JURNAL PUNDI, 2020)
The government estimates that the manufacturing industry sector which will slow down in 2017 will experience another depress in 2018, if the company's capability is low then the company's value will also be lowered. This study aims to analyze the influence of the independent board of commissioners, institutional ownership, managerial ownership, board of commissioners, leverage and audit committee on the value of the company in manufacturing companies listed on the Indonesia Stock Exchange for the period 2014-2018. The samples in this study were 8 companies and 40 observations. This research uses the company's annual financial statement data and summary reports from the Indonesia Stock Exchange website. The method of data analysis is panel data regression. The results showed that the independent board of commissioners, board of commissioners, leverage, audit committee had no significant effect on the value of the company (PBV). Institutional ownership and managerial ownership have a positive and significant effect on the value of the company.